The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13287-020-01956-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of stem cell therapy for the early-stage osteonecrosis of femoral head: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Osteonecrosis of femoral head (ONFH) is a seriously degenerative disease with no effective therapies to slow its progression. Several studies have reported short-term efficacy of stem cells on early-stage ONFH. However, its long-term effect was still unclear especially on progression events. This study was performed to evaluate the long-term efficacy and safety of stem cells and analyze its optimal age group and cell number. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
(138 reference statements)
1
22
1
Order By: Relevance
“…Based on current trends, Mont et al [ 23 ] reported that the total number of individuals affected by ONFH is estimated to reach 20 million by next 10 years worldwide. Besides, the increase in annual publications is inseparable from the advances in basic research and clinical trials in recent years [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on current trends, Mont et al [ 23 ] reported that the total number of individuals affected by ONFH is estimated to reach 20 million by next 10 years worldwide. Besides, the increase in annual publications is inseparable from the advances in basic research and clinical trials in recent years [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable aspects in the study include the clinical use of a high dose of expanded autologous MSC (140-million cells total dose), higher than other reported trials. Interestingly, a cell dose of 1 × 10 8 (100 million cells) has been defined in a meta-analysis as a threshold for better effects on disease progression [ 32 ]. This dose safely obtained the clinical and radiological healing of femoral head in our study, both in males and females, despite the limited number of cases in such an early trial.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of ONFH, in 13 RCTs 619patients (855 hips) published, 49 show clear evidence in support of stem cell therapy to slow down the femoral head collapse and total hip replacement. Ideal age is found to be less than 40 years and optimal cell count of 108 for this treatment.…”
Section: Stem Cell Selection and Applicationmentioning
confidence: 99%